Appraising the dielectric properties and the effectiveness of electromagnetic shielding of graphene reinforced silicone rubber nanocomposite - Shinde, Avinash; Siva, Irulappasamy; Munde, Yashwant; Sankar, Irulappasamy; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Gaff, Milan; Hui, David (Walter de Gruyter GmbH, 2023)
The aim of this research is to measure the dielectric properties and electromagnetic interference (EMI) shielding effectiveness (SE) of silicone rubber reinforced with graphene nanoplates. In a two-roll mill, different amounts of graphene are mixed together. This is followed by compression moulding at 170°C and post-curing for 4 h at 200°C. Between 1 MHz and 1 GHz, the waveguide transmission line method and a vector network analyser are used to measure the dielectric and EMI SE parameters. As the amount of graphene is increased from 0 to 7 wt%, AC conductivity goes up, reaching 1.19 × 10 −3 S/cm at 7 wt%. The same composition gives the highest EMI SE of 43.22 dB at 1 GHz. The high-frequency structural simulation of different compositions shows how shielding works, and the results agree with what has been seen in experiments.